Surface displacements and source parameters of the 2003 Bam (Iran) earthquake from Envisat advanced synthetic aperture radar imagery - Funning, G; Parsons, B; Wright, T; Jackson, J; Fielding, E (2005)
The Mw 6.6, 26 December 2003 Bam (Iran) earthquake was one of the first earthquakes for which Envisat advanced synthetic aperture radar (ASAR) data were available. Using interferograms and azimuth offsets from ascending and descending tracks, we construct a three-dimensional displacement field of the deformation due to the earthquake. Elastic dislocation modeling shows that the observed deformation pattern cannot be explained by slip on a single planar fault, which significantly underestimates eastward and upward motions SE of Bam. We find that the deformation pattern observed can be best explained by slip on two subparallel faults. Eighty-five percent of moment release occurred on a previously unknown strike-slip fault running into the center of Bam, with peak slip of over 2 m occurring at a depth of ∼5 km. The remainder occurred as a combination of strike-slip and thrusting motion on a southward extension of the previously mapped Bam Fault ∼5 km to the east. Copyright 2005 by the American Geophysical Union.